Remarkable creatures : a novel - Chevalier, Tracy (Dutton, 2009)
When Mary Anning uncovers an unusual fossilized skeleton in the cliffs near her home on the English coast, she sets the religious fathers on edge, the townspeople to vicious gossip, and the scientific world alight. Luckily, Mary finds an unlikely champion in prickly Elizabeth Philpot, and in the struggle to be recognized in the wider world, Mary and Elizabeth discover that friendship is their greatest ally.